Dancin' in Anson : A History of the Texas Cowboys' Christmas Ball - Carlson, Paul Howard (Book collections on Project MUSE., 2014)
"Celebrating the celebration of the Old West. In the 1880s, there wasn't much in Anson, Texas, in the way of entertainment for the area's cowhands. But Star Hotel operator M.G. Rhodes changed that when he hosted a Grand Ball the weekend before Christmas. A restless traveling salesman, rancher, and poet from New York named William Lawrence Chittenden, a guest at the Star Hotel, was so impressed with the soiree that he penned his observances in the poem "The Cowboys' Christmas Ball." Reenacted annually since 1934 based on Chittenden's poem, the contemporary dances attract people from coast to coast, from Canada, and from across Europe and elsewhere. Since 1993 Grammy Award-winning musical artist Michael Martin Murphey has played at the popular event. Far more than a history of the Jones County dance, Paul Carlson analyzes the long poem, defining the many people and events mentioned and explaining the Jones County landscape Chittenden lays out in his celebrated work. The book covers the evolution of cowboy poetry and places Chittenden and his poem chronologically within the ever-changing western genre. Dancin' in Anson: A History of the Texas Cowboys' Christmas Ball is a novel but refreshing look at a cowboy poet, his poem, and a joyous Christmas-time family event that traces its roots back nearly 130 years"--